O empreendedorismo nas artes e a trajetória internacional de artistas visuais contemporâneos de economias emergentes - Lorca, Mariana Cristina Betti Cury (2021)
This thesis aims to analyze how emerging Brazilian artists in the visual arts segment, representative of a generation graduated in the mid-1980s and 1990s, in São Paulo, entered the international market from the beginning of this millennium. The initial assumption of the study largely explored the concept of Entrepreneurship in Art, conducted by a systematic review of literature on AE (Arts Entrepreneurship, acronym in English), in order to deepen the understanding if, and how, the precepts brought by the theoretical currents of entrepreneurship have been applied and absorbed in the universe of Art, and related to the career performance and internationalization of artists from emerging countries, like Brazil. The thesis methodology is based on the study of multiple cases, in-depth interviews with artists, gallery owners and curators, as well as a vast search of secondary sources, data and publications that culminated in the development of a database, biographical and curricular, compiling the main information of the artists, and which allowed extended knowledge and further investigation in the field. The study brings significant academic and professional management contributions to the Art System, firstly, aiming to consolidate the understanding and theoretical alignment around AE, not only in proposing a theoretical framework to the concept, but, far beyond, extracting from the research and empirical study the real model, provided by an intense discussion and contrast with the theory - and which can provide a solid curricular, disciplinary base in the HEIs (High Educational Institutions), for students of the arts, as well as a guiding line in the conduction of the artist's personal and professional life trajectory.